2020
DOI: 10.3389/fimmu.2020.02149
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4 Links Inflammation and Fibrosis by Reprogramming Monocyte-Derived Dendritic Cells in vitro

Abstract: Fibrosis is a condition shared by numerous inflammatory diseases. Our incomplete understanding of the molecular mechanisms underlying fibrosis has severely hampered effective drug development. CXCL4 is associated with the onset and extent of fibrosis development in multiple inflammatory and fibrotic diseases. Here, we used monocyte-derived cells as a model system to study the effects of CXCL4 exposure on dendritic cell development by integrating 65 longitudinal and paired whole genome transcriptional and methy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 70 publications
3
29
1
Order By: Relevance
“…It is tempting to speculate on an active involvement of CXCL4 in transcriptional processes. In monocytes/macrophages, CXCL4 is able to induce considerable changes in the transcriptional landscape, leading to pro-inflammatory and pro-fibrotic phenotypes [ 42 , 43 ]. It is worth noting that unlike other chemokines, no single receptor has been identified that explains all CXCL4 functions.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to speculate on an active involvement of CXCL4 in transcriptional processes. In monocytes/macrophages, CXCL4 is able to induce considerable changes in the transcriptional landscape, leading to pro-inflammatory and pro-fibrotic phenotypes [ 42 , 43 ]. It is worth noting that unlike other chemokines, no single receptor has been identified that explains all CXCL4 functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, using RegEnrich pipeline, we predicted a network of key regulators that leads monocyte-derived dendritic cells (moDCs) to differentiate into a different trajectory upon CXCL4 stimulation, compared to the moDCs without CXCL4 stimulation. We also experimentally validated RegEnrich pipeline's prediction by silencing one of the top-ranked regulators in the predicted network, i.e., CIITA 52 . More recently, we studied the mechanism of human T regulatory (Treg) cells programming under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…CD11b + DCs have been found to upregulate the expression of several MMPs, promoting collagen and ECM degradation (171). CXCL4 has recently been identified to be crucial in altering DC development into a pro-inflammatory and pro-fibrotic phenotype that induces ECM accumulation and MFT (172).…”
Section: Dendritic Cellsmentioning
confidence: 99%